Bilateral Synchronization of Hippocampal Early Sharp Waves in Neonatal Rats - Valeeva, Guzel; Nasretdinov, Azat; Rychkova, Veronika; Khazipov, Roustem (Frontiers in Cellular Neuroscience, 2019)
In the neonatal rodent hippocampus, the first and predominant pattern of correlated neuronal network activity is early Sharp Waves (eSPWs). Whether and how eSPWs are organized bilaterally remains unknown. Here, using simultaneous silicone probe recordings from the left and right hippocampus in neonatal rats in vivo we found that eSPWs are highly synchronized bilaterally with nearly zero time lag between the two sides. The amplitudes of eSPWs in the left and right hippocampi were also highly correlated. eSPWs also supported bilateral synchronization of multiple unit activity. We suggest that bilateral correlated activity supported by synchronized eSPWs participates in the formation of bilateral connections in the hippocampal system.